Alan Turing's Other Universal Machine. (Communications of the ACM, 2012)
The article discusses the Automatic Computing Engine (ACE), a stored program computer proposed by the computer scientist Alan Turing in 1946, examining its design and influence. The author examines the ACE's use of mercury delay-line memory, optimum programming, and multiple registers. The article discusses the importance of ACE derivatives such as the English Electric Company's DEUCE and the Bendix Aviation Corporation's Bendix G-15 and argues that ACE influenced computer design.